Heat transfer analysis of MHD stagnation point flow over a stretching sheet with Convective Boundary Conditions - R. N. Jat; Navin Kumar (International Journal of Mathematics And its Applications, 2016)
The problem of a steady two dimensional MHD stagnation point flow and heat transfer analysis over a stretching sheet with CBC and NH is considered. The governing partial differential equation are transformed in to ordinary differential equation using a similarity transformation. Numerical solution are obtained for the skin friction coefficient, the surface temperature, nusselt number as well as the velocity temperature and velocity profiles. The features of the flow and heat transfer characteristics for various values of the Prandtl number, stretching parameter, magnetic parameter and conjugate parameter are analyzed and discussed.